Rethinking Refugees as Economically Isolated: The Rohingyas Participation in Informal Economy in Klang Valley, Malaysia - Ab. Wahab, Andika (JAS (Journal of ASEAN Studies), 2017)
Unlike economic migrants, the refugee population is often portrayed as a burden to hosting governments. They are seen to be economically passive and highly dependent on the hosting government’s generosity and international organizations and donors’ humanitarian assistances. In Malaysia, refugee population including the Rohingyas are no longer living in sprawling tents, isolated villages or any refugee settlement in remote areas. They make their way to semi-urban and major city areas in search of economic opportunities to make a living while waiting for durable solutions accorded to them. The absence of the right to work coupled with the mounting pressure to make a living caused the Rohingyas to engage in informal economy, undertaking a variety of occupations and income-generating activities albeit risks of arrest and exploitation. This study aims to analyze the relationship between the Rohingyas’ participation in informal economy and their livelihood. Resulting from two series of field works engaging the Rohingyas in Klang Valley between 2013 and 2016, the study found that despite the absence of their right to work, the Rohingyas persistently entered into informal labor market as temporary, unskilled and low wage workers in various sectors such as trade, services and automotive. For the self-employed Rohingyas, they tend to engage in small-scale and unregulated income generating activities. Their goods and services are offered beyond the needs of the Rohingyas but to a larger extent of consumers including other migrant groups and local community. The Rohingyas’ active participation in informal economy is an attempt to not dependent or less depend on the UNHCR’s assistance and government’s generosity. This debunks the misconception that the Rohingya population in Malaysia are physically and economically isolated from the domestic economic structure.